Evaluation of the efficacy of an autogenous Escherichia coli vaccine in broiler breeders. Issue 3 (4th May 2017) - Li, Lili; Thøfner, Ida; Christensen, Jens Peter; Ronco, Troels; Pedersen, Karl; Olsen, Rikke H.
ABSTRACT: In poultry production Escherichia coli autogenous vaccines are often used. However, the efficacy of autogenous E. coli vaccinations has not been evaluated experimentally in chickens after start of lay. The aim of the present study was to evaluate the protective effect of an autogenous E. coli vaccine in broiler breeders. Three groups of 28-week-old broiler breeders (unvaccinated, vaccinated once and twice, respectively) were challenged with a homologous E. coli strain (same strain as included in the vaccine) or a heterologous challenge strain in an experimental ascending model. The clinical outcome was most pronounced in the unvaccinated group; however, the vast majority of chickens in the vaccinated groups had severe pathological manifestations similar to findings in the unvaccinated group after challenge with a homologous as well as a heterologous E. coli strain. Although significant titre rises in IgY antibodies were observed in the twice vaccinated group, antibodies did not confer significant protection in terms of pathological impact. Neither could transfer of maternal-derived antibodies to offspring be demonstrated. In conclusion, with the use of the present model for ascending infection, significant protection of an autogenous E. coli vaccine against neither a homologous nor a heterologous E. coli challenge could not be documented.